RANCANG BANGUN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN KODULAR PADA MATERI PERUBAHAN BENTUK ENERGI KELAS IV SEKOLAH DASAR - Novita sari; Ahmad Syarif; Issaura Sherly Pamela (Jurnal Tunas Pendidikan, 2026)
This research  aims to describe the development process, level of validity, and level of practicality of interactive learning media assisted by Kodular on the material of energy transformation in grade IV of Elementary School. This research uses the Research and Development (R&D) method with the Lee and Owens development model which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques are carried out through interview sheets, validation questionnaires by experts, and practicality questionnaires by teachers and students. The results of media validation were carried out in two stages with an average value of 4 with the "valid" category in the first stage and 4.46 with the "very valid" category in the second stage. Material validation also showed an increase from an average of 4.58 with the "very valid" category to 4.83 with the "very valid" category, while language validation increased from an average of 3.7 with the "valid" category to 4.5 with the "very valid" category after revision. In addition, the results of the practicality test can be seen based on the results of the teacher response questionnaire which obtained an average score of 4.8 with the category "very practical" and the student questionnaire showed that in the small group trial an average score of 4.26 was obtained with the category "very practical", and in the large group trial an average score of 4.38 was obtained with the category "very practical".